The Effect Of E-Human Resources Management On Organizational Performance From Public Sectors’ Perspectives - Wondimu Tadesse Dawo, Dr.Paidipati Gopala Krishna Murthy, (European Economic Letters (EEL), 2025)
Effective human resources management (HRM) plays a vital role in shaping organizational performance and success. Traditionally, HRM practices have been predominantly paper-based, time-consuming, and prone to errors. However, the advent of e-HRM, which leverages digital technologies and online platforms, has revolutionized HRM processes, offering numerous advantages to organizations. This study investigated the effect of electronic human resource management (e-HRM) on organizational performance. Both descriptive and explanatory approaches, utilizing a quantitative research methodology were employed. The sample selection was conducted using a simple random sampling technique. The data were analyzed using descriptive and inferential statistical tools. Descriptive statistics, correlation, and multiple regression analysis were performed to test the hypothesized relationships between the independent and dependent variables. The regression results shows that all the E-HRM dimensions (E-Recruitment and Selection, E-Training, E-Performance Appraisal, and E-Compensation System) have a positive and statistically significant effect on Organizational Performance in the public sector context. The strongest effects are observed for E- Performance Appraisal and E-Compensation and Rewards, suggesting that these E-HRM practices play a pivotal role in improving organizational performance. To address these findings, the public sectors should focus on improving e-recruitment processes by utilizing objective algorithms and paperless approaches. Furthermore, it is recommended to prioritize the implementation of e-training programs supported by digital technology, adopt online pay practices and automate compensation systems, and leverage digital technology in performance appraisal processes.